2018
DOI: 10.1016/j.cdtm.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of major cardiovascular risk factors is associated with arterial stiffness in adults

Abstract: ObjectiveCardiovascular disease (CVD) is the leading cause of mortality and morbidity worldwide. Previous studies have indicated that clustering of major CVD risk factors is common. We aimed to explore the association of clustering of CVD risk factors with arterial stiffness in adults.MethodsA total of 9984 adults were enrolled. We investigated clustering of four major CVD risk factors (defined as two or more of the following: hypertension, diabetes, dyslipidemia, and high body mass index) and their associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Consequently, total risk of CVD is the sum of respective risks arising from the incidence of major CRFs. [10][11][12][13][14] The estimated risk of a CVD increases with the emergence of an additional CRF. 15 Age is also frequently allocated into the same category.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, total risk of CVD is the sum of respective risks arising from the incidence of major CRFs. [10][11][12][13][14] The estimated risk of a CVD increases with the emergence of an additional CRF. 15 Age is also frequently allocated into the same category.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported prevalence of clusters of CVD risk factors in the general population. [19][20][21] Few studies have identified cluster types based on sleep pattern 22 , behavioural characteristics 23 , and cardiometabolic health 24 in CMVDs, yet little is known about clusters of CVDs risk factors among CMVDs; though the prevalence of these risk factors have been well described in this group. 25,26 Evidence-based practices have shown that chronic diseases such as hypertension, diabetes, and hyperlipidemia are better treated together since they often occur in clusters.…”
Section: Introductionmentioning
confidence: 99%
“… 39 , 40 The clustering of CVD risk factors has been significantly correlated with arterial stiffness. 41 Jeanclos et al 42 also suggested that telomere shortening was associated with hypertension, endothelial dysfunction, atherosclerosis, and cardiovascular mortality. In patients with CKD, due to oxidative stress and inflammation, vascular calcification can be aggravated, which increases the risk of CVD, a phenomenon that can also be reflected by the shortened telomere length.…”
Section: Discussionmentioning
confidence: 99%